Estágio de operações em marketing digital - estrategista de contas - Vieira, Daniel Sousa de Pinho (Universidade Federal de São Carlos, 2021)
I had the opportunity to do an internship in the area of media operations at Calina Marketing Digital, where I performed functions with a lot of data analysis, aiming to have insights to improve our clients' sales, and also a lot of project management, to put these insights into execution in an assertive action plan. In this work, you will see a context about the market and services provided, as well as the daily work in this scope of management and analysis.
Internship in digital marketing operations
Keywords: Marketing digital; Análise de dados; Gestão de Projetos; Digital marketing; Data analysis; Projects management; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS